2020
DOI: 10.1177/2040622320912661
|View full text |Cite
|
Sign up to set email alerts
|

D-mannose attenuates bone loss in mice via Treg cell proliferation and gut microbiota-dependent anti-inflammatory effects

Abstract: Background: D-mannose exhibits strong anti-inflammatory properties, but whether it has beneficial effects on preventing and treating osteoporosis remains unknown. Methods: Female, 12-month-old senile C57BL6/J mice (s-Man group) and 8-week-old ovariectomized C57BL6/J mice (OVX-Man group) were treated with D-mannose in drinking water for 2 months (six mice/group). Microcomputed tomography analysis and hematoxylin and eosin staining were performed to investigate the effect of D-mannose on attenuation of bone loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Consistent with these findings, mannose treatment increased Bacteroidetes and also reduced gene expression of inflammatory markers ( Tnfa and Ifng ) in adipocytes of HFD mice ( 20 ). Another study also reported that mannose treatment attenuated bone loss induced by senility and estrogen deficiency in mice, via the increase of Treg cells and Bacteroidetes ( 44 ). These findings suggest mannose treatment has gut microbiota-dependent anti-inflammatory effects.…”
Section: Regulatory Functions Of Mannose In Inflammationmentioning
confidence: 97%
“…Consistent with these findings, mannose treatment increased Bacteroidetes and also reduced gene expression of inflammatory markers ( Tnfa and Ifng ) in adipocytes of HFD mice ( 20 ). Another study also reported that mannose treatment attenuated bone loss induced by senility and estrogen deficiency in mice, via the increase of Treg cells and Bacteroidetes ( 44 ). These findings suggest mannose treatment has gut microbiota-dependent anti-inflammatory effects.…”
Section: Regulatory Functions Of Mannose In Inflammationmentioning
confidence: 97%
“…Besides that, the osteogenic medium contained 2 mM β -glycerophosphate (Sigma-Aldrich, St. Louis, MO), 10 nM dexamethasone (Sigma-Aldrich, St. Louis, MO), and 100 μ M L-ascorbic acid 2-phosphate (Wako Chemicals USA, Richmond, VA). All the medium preparation methods are based on the methods in [ 12 , 15 ] and our previous studies [ 13 ]. Total RNA was extracted from each group with the TRIzol reagent (Invitrogen, Carlsbad, CA, USA) after ten days of inducement, and the gene expression levels of Bglap and Alpl were assayed by real-time PCR analysis.…”
Section: Methodsmentioning
confidence: 99%
“…B cell depletion via rituximab reduced synovial RANKL, expression of RANK + osteoblasts, and sera levels of bone turnover markers in patients with inflammatory OP (Wheater et al, 2011 ; Boumans et al, 2012 ). In ovariectomized and post-menopausal murine models of OP, administration of D-mannose (Liu et al, 2020 ), Bacillus calusii (Dar et al, 2018a ), and Lactobacillus acidophilus (Dar et al, 2018b ) attenuated bone loss, reduced expression of pro-inflammatory cytokines IL-6, IL-17, TNF-α, and IFN-γ, and increased expression of anti-osteoclastogenic factor IL-10 by stimulating the proliferation of Treg cells, restoring Treg/Th17 balance. Antibody-based TNF-α inhibition in a rat model of OP elevated bone density, simultaneously increased and decreased OPG and RANKL expression, respectively, and enhanced osteogenic differentiation of endogenous stromal cells (Yu et al, 2019 ).…”
Section: Inflammatory Ad Comorbiditiesmentioning
confidence: 99%